Clinical outcomes of patients with pT4a and pT4b oral cavity squamous cell carcinoma who had undergone surgery: Results from a Taiwanese registry-based, nationwide cohort study. (March 2022) - Kang, Chung-Jan; Wen, Yu-Wen; Lee, Shu-Ru; Ng, Shu-Hang; Lee, Li-Ang; Lee, Li-Yu; Hsueh, Chuen; Lin, Chien-Yu; Fan, Kang-Hsing; Wang, Hung-Ming; Hsieh, Chia-Hsun; Yeh, Chih-Hua; et al.
Highlights: NCCN guidelines maintain that T4b OCSCC should be treated with non-surgical approach. The 5-year survival rates were more favorable in patients with pT4a than pT4b OCSCC. Compared with pT4a, pT4b tumors had a higher burden of pathological risk factors. After PS matching, no outcome difference between pT4b and pT4a OCSCC was observed. T4b OCSCC should undergo initial surgical excision if adequate resection is possible. Abstract: Objectives: While the NCCN guidelines maintain that T4b oral cavity squamous cell carcinoma (OCSCC) should undergo either non-surgical treatments or clinical trials, promising outcomes of T4b OCSCC having surgical excision have been reported. We analyzed and compared the clinical outcomes of Taiwanese patients with pT4a and pT4b OCSCC who had undergone surgical treatment. Methods: From 2011 to 2017, a total of 4031 and 355 patients with first primary pT4a and pT4b OCSCC were identified. A propensity score (PS)-matched analysis of patients (n = 351 each) for pT4a and pT4b tumors was also performed. Results: The 5-year disease-specific and overall survival (DSS/OS) rates were more favorable in patients with pT4a than in those with pT4b OCSCC (64% / 55%, p < 0.0001; 55% / 43%, p < 0.0001, respectively). Compared with pT4a, those with pT4b tumors had a higher burden of the following risk factors: buccal/retromolar/hard palate subsite, male sex, depth ≥ 10 mm, and positive margins. Before PS matching, multivariable analyses revealed that pT4b tumors ( versus pT4a) were an adverse prognosticator for both 5-year DSS and OS (hazard ratios: 1.32 and 1.39, respectively). However, in the PS-matched cohort, no significant differences in 5-year DSS and OS rates were observed between pT4a and pT4b OCSCC (57% / 56%, p = 0.4024; 48% / 44%, p = 0.1807, respectively) Conclusions: No significant outcome differences were evident between pT4b and pT4a OCSCC after PS matching. The most plausible hypothesis for the observed survival difference between T4a and T4b tumors is that it was driven by positive margins. We suggest that T4b OCSCC should undergo initial surgical excision if adequate resection is possible.